Competence evaluation processes for nursing students abroad: Findings from an international case study. (April 2017) - Tommasini, Cristina; Dobrowolska, Beata; Zarzycka, Danuta; Bacatum, Claudia; Bruun, Anne Marie Gran; Korsath, Dag; Roel, Siv; Jansen, Mette Bro; Milling, Tine; Deschamps, Anne; Mantzoukas, Stefanos; Mantzouka, Christine; et al.
Abstract: Background: Assessing clinical competence in nursing students abroad is a challenge, and requires both methods and instruments capable of capturing the multidimensional nature of the clinical competences acquired. Objectives: The aim of the study was to compare the clinical competence assessment processes and instruments adopted for nursing students during their clinical placement abroad. Design: A case study design was adopted in 2015. Setting and Participants: A purposeful sample of eight nursing programmes located in seven countries (Belgium, Denmark, Greece, Norway, Poland, Portugal and Italy) were approached. Methods: Tools as instruments for evaluating competences developed in clinical training by international nursing students, and written procedures aimed at guiding the evaluation process, were scrutinised through a content analysis method. Findings: All clinical competence evaluation procedures and instruments used in the nursing programmes involved were provided in English. A final evaluation of the competences was expected by all nursing programmes at the end of the clinical placement, while only four provided an intermediate evaluation. Great variability emerged in the tools, with between five and 88 items included. Through content analysis, 196 items emerged, classified into 12 different core competence categories, the majority were categorised as 'Technical skills' (= 60), 'Self-learning and critical thinking' (= 27) and 'Nursing care process' (= 25) competences. Little emphasis was given in the tools to competences involving 'Self-adaptation', 'Inter-professional skills', 'Clinical documentation', 'Managing nursing care', 'Patient communication', and 'Theory and practice integration'. Conclusions: Institutions signing Bilateral Agreements should agree upon the competences expected from students during their clinical education abroad. The tools used in the process, as well as the role expected by the student, should also be agreed upon. Intercultural competences should be further addressed in the process of evaluation, in addition to adaptation to different settings. There is also a need to establish those competences achievable or not in the host country, aiming at increasing transparency in learning expectations and evaluation. Highlights: Nursing students' participation in exchanges in international programs, is considered an important learning occasion, which should be encouraged and promoted. Strategies, methods and tools for evaluating the competences acquired while learning abroad, require further discussion and study at least between the host and home country.